Factors Associated With Travel Distance in the Receipt of Proton Breast Radiation Therapy - Sylvia S. Rhodes, BA; Eva Berlin, MD; Nikhil Yegya-Raman, MD; Abigail Doucette, MPH; Michelle Gentile, MD, PhD; Gary M. Freedman, MD; Neil K. Taunk, MD, MSCTS (International Journal of Particle Therapy, 2022)
Introduction: Proton radiation therapy (PBT) may reduce cardiac doses in breast cancer treatment. Limited availability of proton facilities could require significant travel distances. This study assessed factors associated with travel distances for breast PBT. Materials and Methods: Patients receiving breast PBT at the University of Pennsylvania from 2010 to 2021 were identified. Demographic, cancer, and treatment characteristics were summarized. Straight-line travel distances from the department to patients’ addresses were calculated using BatchGeo. Median and mean travel distances were reported. Given non-normality of distribution of travel distances, Wilcoxon rank sum or Kruskal-Wallis test was used to determine whether travel distances differed by race, clinical trial participation, disease laterality, recurrence, and prior radiation. Results: Of 1 male and 284 female patients, 67.8% were White and 21.7% Black. Median travel distance was 13.5 miles with interquartile range of 6.1 to 24.8 miles, and mean travel distance was 13.5 miles with standard deviation of 261.4 miles. 81.1% of patients traveled less than 30 and 6.0% more than 100 miles. Black patients’ travel distances were significantly shorter than White patients’ and non-Black or non-White patients’ travel distances (median = 4.5, 16.5, and 11.3 miles, respectively; P < .0001). Patients not on clinical trials traveled more those on clinical trials (median = 14.7 and 10.2 miles, respectively; P = .032). There was no difference found between travel distances of patients with left-sided versus right-sided versus bilateral disease (P = .175), with versus without recurrent disease (P = .057), or with versus without prior radiation (P = .23). Conclusion: This study described travel distances and demographic and clinicopathologic characteristics of patients receiving breast PBT at the University of Pennsylvania. Black patients traveled less than White and non-Black or non-White patients and comprised a small portion of the cohort, suggesting barriers to travel and PBT. Patients did not travel further to receive PBT for left-sided or recurrent disease.